La calidad, más que una moda, un reto en la Europa de la Sociedad del Conocimiento: la mejora continua más allá de los modelos y las certificaciones (competencias de un formador que aseguran la calidad). - Domínguez Fernández, Guillermo; Lozano Pérez, Luz (Revista Complutense de Educación, 2005)
A new organizing scenario has been consolidated in Europe during the last years: the Knowledge Society. Converging on this evolution, another quality certifying and management systems have been established. To many training institutions, this framework has brought as consequence a higher necessity to homologate or certify their programs with some quality system. However, training is a different service and needs specific patterns or at least less special adaptations to be, besides an image, a real improvement process of training and development of participant people in those training actions On this framework, the quality concept is polysemous but also full of intentionality. In this work we defend a model of quality based on the transference of learning and the social impact of training, which fundamental aim must be the fight against the inequality and the training like second opportunity. The model we propose, model VERO (Organizacional Verification), has that objective, but as it can be deduced, it is also a model that responds to the different models of quality on a European-wide framework: (EFQM) and the ISO 9000 Quality Management System Certification.
Keywords: Quality; Continuing Vocational Training; ISO standards; European Foundation for Quality Management (EFQM); Methods of self-assessment